1995
DOI: 10.1520/jfs13881j
|View full text |Cite
|
Sign up to set email alerts
|

Casework Experience of GSR Detection in Israel, on Samples from Hands, Hair, and Clothing Using an Autosearch SEM/EDX System

Abstract: Casework experience in the detection of GSR particles on samples from hands, hair and clothing is reported for the period of 6 years (1989–1994). The overall “success” rate on the examined samples is about 10%. Aspects of the sampling procedures, the number of particles detected per sample and problems of possible contamination are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…In this context it is worth pointing out the success rate of detection of GSR particles on samples from suspects and their clothing in casework. Recent studies on this subject [27,28] have shown the success rate is approximately 10%. Among positive samples (of casework in Israel), moreover, a high percentage (39%) had only one GSR particle, 44% had only few (2-5) particles and only 17% had more than five particles.…”
Section: Compositions Classification and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it is worth pointing out the success rate of detection of GSR particles on samples from suspects and their clothing in casework. Recent studies on this subject [27,28] have shown the success rate is approximately 10%. Among positive samples (of casework in Israel), moreover, a high percentage (39%) had only one GSR particle, 44% had only few (2-5) particles and only 17% had more than five particles.…”
Section: Compositions Classification and Interpretationmentioning
confidence: 99%
“…It seems that use of this method to examine the hands of someone suspected of shooting cannot contribute significant information unless he was arrested immediately after the incident, which is far from a realistic scenario. In casework the shooter might, at best, be arrested several hours after the incident, so very few, if any, GSR particles are left on his hands [28]. In such a situation the distribution pattern has no meaning.…”
Section: Sampling Of Gsr and Their Persistence On Different Surfacesmentioning
confidence: 99%
“…A coleta foi realizada nas mãos dos atiradores por meio da técni-ca de esfregaço 20,21 , em períodos de até 1 h após os disparos, utilizando-se cotonetes embebidos em solução diluída de EDTA a 2%. Aplicou-se a solução complexante 22,23 em quatro regiões distintas da mão, abrangendo a palma, o dorso e a região palmar (Pinça-Palmar) e dorsal (Pinça-Dorsal) dos dedos polegar e indicador 24 , conforme Figuras 2(a-d).…”
Section: Coleta E Acondicionamento De Resíduos De Disparosunclassified
“…The residues escape from the firearm essentially through the barrel although other openings may also be involved, such as ejection ports of self-loading or automatic firearms or the space between the barrel and the chamber in revolvers. This means that GSR particles may deposit on surfaces in the vicinity of the discharging firearm -typically, a shooter's or bystander's hands, clothing, face and head hair [2]. The search, detection and identification of GSR particles is therefore regularly conducted when individuals (or items belonging to individuals) are suspected of having been involved in a shooting incident.…”
Section: Introductionmentioning
confidence: 99%
“…This resorts from a number of studies [5-10, e.g.]. Additional circumstantial information, such as the place where the shooting took place (indoors or outdoors) and meteorological conditions should also be considered [2].…”
Section: Introductionmentioning
confidence: 99%